Cement Dust Exposure and Perturbations in Some Elements and Lung and Liver Functions of Cement Factory Workers - Egbe Edmund Richard; Nsonwu-Anyanwu Augusta Chinyere; Offor Sunday Jeremaiah; Usoro Chinyere Adanna Opara; Etukudo Maise Henrieta; Egbe Deborah Ifunanya (Journal of Toxicology)
Background. Cement dust inhalation is associated with deleterious health effects. The impact of cement dust exposure on the peak expiratory flow rate (PEFR), liver function, and some serum elements in workers and residents near cement factory were assessed. Methods. Two hundred and ten subjects (50 workers, 60 residents, and 100 controls) aged 18–60 years were studied. PEFR, liver function {aspartate and alanine transaminases (AST and ALT) and total and conjugated bilirubin (TB and CB)}, and serum elements {lead (Pb), copper (Cu), manganese (Mn), iron (Fe), cadmium (Cd), selenium (Se), chromium (Cr), zinc (Zn), and arsenic (As)} were determined using peak flow meter, colorimetry, and atomic absorption spectrometry, respectively. Data were analysed using ANOVA and correlation at p=0.05. Results. The ALT, TB, CB, Pb, As, Cd, Cr, Se, Mn, and Cu were significantly higher and PEFR, Fe, and Zn lower in workers and residents compared to controls (p<0.05). Higher levels of ALT, AST, and Fe and lower levels of Pb, Cd, Cr, Se, Mn, and Cu were seen in cement workers compared to residents (p<0.05). Negative correlation was observed between duration of exposure and PEFR (r=-0.416, p=0.016) in cement workers. Conclusions. Cement dust inhalation may be associated with alterations in serum elements levels and lung and liver functions while long term exposure lowers peak expiratory flow rate.